2021
DOI: 10.3390/biomedicines9091269
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Angiogenesis in the Pathogenesis of Coronary Aneurysms

Abstract: The present study aimed to evaluate the plasma concentration of pro and antiangiogenic factors and their role in the pathogenesis of coronary artery abnormal dilation (CAAD). We measured the plasma concentration of matrix metalloproteinase-8 (MMP-8), transforming growth factor beta 1 (TGF-β1), Angiopoietin-2, vascular endothelial growth factor (VEGF), and fibroblast growth factor (FGF) using a sandwich ELISA technique in the plasma of patients with coronary artery abnormal dilation (CAAD, Group 1), coronary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The results obtained in the presented study suggest that the previously reported increased signaling of VEGF-A in AAA tissues is probably reflected in higher plasma levels of VEGF-A, but not in altered expression of VEGFA in PBMCs. This conclusion could be supported by other studies, in which elevated plasma levels of VEGF-A were found in aneurysmal diseases [64][65][66][67].…”
Section: Discussionsupporting
confidence: 81%
“…The results obtained in the presented study suggest that the previously reported increased signaling of VEGF-A in AAA tissues is probably reflected in higher plasma levels of VEGF-A, but not in altered expression of VEGFA in PBMCs. This conclusion could be supported by other studies, in which elevated plasma levels of VEGF-A were found in aneurysmal diseases [64][65][66][67].…”
Section: Discussionsupporting
confidence: 81%
“…Adverse vascular remodeling is considered to be a possible mechanism of CAAD development. [13][14][15] Therefore, assuming that the processes mentioned above involve the entire vascular bed, coronary microcirculation remodeling is thought to be a possible cause of CMD in CAAD patients. Moreover, a turbulent blood flow in aneurysms supports the development of thrombi, which may result in distal embolization and thus impair coronary microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was found that C-peptide inhibited the synthesis of collagen type IV (COL4), which is one of the building blocks of the extracellular matrix [34]. e angiogenesis process has been also implicated in the pathogenesis of CAE [35,36]. In a study by Lim et al, C-peptide was found to accelerate angiogenesis through stimulation of extracellular signalregulated kinase (ERK 1/2), Akt, and NO production using human umbilical vein endothelial cells (HUVEC) [37].…”
Section: Dicussionmentioning
confidence: 99%